2021
DOI: 10.17066/tpdrd.1050739
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’deki Psikolojik Danışman Eğitiminde Kritik Akreditasyon Konuları ile İlgili Öğretim Elemanları Görüşlerinin İncelemesi

Abstract: The lack of counselor education standards set by professional organizations increases the necessity for accreditation studies. Therefore, this descriptive study aimed to investigate the opinions of counselor educators working in Turkish public and private universities' counselor education programs on critical standards/criteria of the accreditation process. A total of 201 counselor educators aged between 24 to 88 years participated in the study. Data were collected through a demographic form as well as a surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In contrast, in Türkiye, while counsellor education programmes may adhere to the CoHE's curricula, there appears to be a lack of established supervision standards for counsellor educators to follow. This finding underscores the need for an independent accreditation body in Türkiye, aligning with the findings of previous research (Kalkan & Can, 2019;Özyürek, 2009;Özyürek et al, 2021). Momentum towards a counsellor education and supervision accreditation institution in Türkiye is growing.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, in Türkiye, while counsellor education programmes may adhere to the CoHE's curricula, there appears to be a lack of established supervision standards for counsellor educators to follow. This finding underscores the need for an independent accreditation body in Türkiye, aligning with the findings of previous research (Kalkan & Can, 2019;Özyürek, 2009;Özyürek et al, 2021). Momentum towards a counsellor education and supervision accreditation institution in Türkiye is growing.…”
Section: Discussionsupporting
confidence: 88%
“…Researchers in Türkiye have explored various aspects of the supervision process in the context of school counselling internships (Özyürek, 2009, 2010), individual counselling group supervision experiences (Koçyiğit, 2020), online supervision encounters (Özyiğit & Atik, 2021), and efforts to standardize counselling supervision practices nationwide (Kalkan & Can, 2019;Özyürek et al, 2021). In a national survey involving 365 senior counselling trainees, Özyürek (2009) revealed that Turkish counselling students frequently reported deficiencies and inconsistencies in their supervision experiences, and inadequately trained counsellor educators providing supervision in unwieldy supervision groups.…”
Section: Supervision Of Counsellor Trainees In the Us And Türkiyementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been found that undergraduate education is insufficient in gaining counseling and supervision skills (Sakız et al, 2020). To overcome these deep-rooted problems, competencies and accreditation studies are continuing in Türkiye (Özyürek et al, 2021).…”
Section: Introductionmentioning
confidence: 99%